ANALISIS FAKTOR INTERNAL DAN EKTERNAL PERUSAHAAN TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN MANUFAKTUR DI BURSA EFEK INDONESIA - ROSY T.W., M. THERESIA (Kajian Ilmiah Mahasiswa Manajemen, 2013)
Every company should be able to survive by increasing the company’s profits and increase shareholder wealth so as to increase the firm value. Based on previous research there are two factors that affect the firm value internal and external factors. In this study the internal factors are profitability, dividend policy and debt. The external factors are market growth and the inflation rate. The population of this study is manufacturing listed on the stock exchange in 2009 until 2011 with a total sample of 29 manufacturing companies those obtained from www.idx.co.id. To answer the research problem and hypothesis testing with a panel regression method. The results of this study indicate that internal factors consisting of dividend policy and debt have a positive significant effect on the firm value but profitability have no effect on the firm value. The external factor consisting of inflation rate have a negative significant effect on the firm value but market growth have no effect on the firm value.